Between unemployment and enterprise in neoliberal India: Educated youth creating work in the private education sector. Issue 4 (12th January 2020) - Deuchar, Andrew; Dyson, Jane
Abstract : This paper draws on ethnographic material to analyse how unemployed youth create work in the private educational sector. It shows how a set of educated young men, who moved from rural areas to a north Indian city to find work, are seeking to create jobs after an extended period of unemployment. Having attended coaching clinics and private tuition centres to prepare for white‐collar jobs, they draw on the experience, knowledge, and skills they have gained to create work in those same institutions. They do so by running errands and creating services for institutions, as well as undertaking administrative duties and teaching classes. Our main argument is that young men creatively engage with notions of enterprise to make an income and acquire a measure of respect. Studies of enterprise culture and neoliberal subjectivity formation often emphasise how individuals shore up their own value by competing with others and promoting their own interests. But we highlight how youth also maintain their value by making sense of their strategies in terms of assisting other young people. At the same time, however, their practises work to reproduce gender norms and class inequalities. Abstract : This paper draws on ethnographic material to analyse how unemployed youth create work in the private educational sector in north India. Our main argument is that young men creatively engage with notions of enterprise to make an income and acquire a measure of respect. Studies of enterprise culture and neoliberal subjectivity formation often emphasise how individuals shore up their own value by competing with others and promoting their own interests, but we highlight how youth also maintain their value by making sense of their strategies in terms of assisting other young people.